2022
DOI: 10.1136/jitc-2021-003831
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity and safety of camrelizumab plus famitinib in patients with platinum-resistant recurrent ovarian cancer: results from an open-label, multicenter phase 2 basket study

Abstract: BackgroundCombination treatments with immune-checkpoint inhibitor and antiangiogenic therapy have the potential for synergistic activity through modulation of the microenvironment and represent a notable therapeutic strategy in recurrent ovarian cancer (ROC). We report the results of camrelizumab (an anti-programmed cell death protein-1 antibody) in combination with famitinib (a receptor tyrosine kinase inhibitor) for the treatment of platinum-resistant ROC from an open-label, multicenter, phase 2 basket trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
7
22
0
Order By: Relevance
“…Reactive capillary endothelial proliferation is a common skin toxicity associated with camrelizumab 28 ; hand-foot syndrome, hypertension, and proteinuria are likely to be associated with famitinib 25 . The incidence of reactive capillary endothelial proliferation in this study was substantially reduced compared with that of camrelizumab monotherapy; this finding was in line with those from other studies that combined camrelizumab with anti-angiogenic agents 27,[29][30][31] . This indicates that the camrelizumabregulated immune response may destroy the dynamic balance between pro-and anti-angiogenic factors.…”
Section: Discussionsupporting
confidence: 91%
“…Reactive capillary endothelial proliferation is a common skin toxicity associated with camrelizumab 28 ; hand-foot syndrome, hypertension, and proteinuria are likely to be associated with famitinib 25 . The incidence of reactive capillary endothelial proliferation in this study was substantially reduced compared with that of camrelizumab monotherapy; this finding was in line with those from other studies that combined camrelizumab with anti-angiogenic agents 27,[29][30][31] . This indicates that the camrelizumabregulated immune response may destroy the dynamic balance between pro-and anti-angiogenic factors.…”
Section: Discussionsupporting
confidence: 91%
“…Antiangiogenic therapy and immunotherapy both act on the tumor microenvironment, and previous preclinical studies have shown that immunotherapy combined with anti-angiogenic drugs synergistically inhibit tumor growth and metastasis ( 33 ). Some clinical trials also confirmed the value of antiangiogenic therapy in combination with immunotherapy ( 34 , 35 ). However, the application of anlotinib combined with ICIs in breast cancer has not yet been reported, our present study shows that anlotinib combined with immunotherapy has also achieved good clinical efficacy in metastatic breast cancer.…”
Section: Discussionmentioning
confidence: 84%
“…At the cut-off date, 24.3% of patients achieved CR or PR. The median PFS and OS of this group of patients were 4.1 months and 18.9 months, respectively ( 74 ). Sintilimab plus anlotinib was demonstrated efficacy as second-line or later therapy for patients with PD-L1-positive advanced cervical cancer in a phase II trial, with an ORR of 54.8% (23/42) ( 75 ).…”
Section: Clinical Trials About the Dual Inhibition Of Vegf/vegfr And ...mentioning
confidence: 95%
“…The results from a multicenter phase II basket trial (NCT03827837) showed that the camrelizumab plus famitinib exhibited antitumor activity in patients with platinum-resistant ovarian cancer (OC) ( 74 ). At the cut-off date, 24.3% of patients achieved CR or PR.…”
Section: Clinical Trials About the Dual Inhibition Of Vegf/vegfr And ...mentioning
confidence: 99%